New Material of Thylacocephala from the Early Ladinian (Middle Triassic) of Northern Grigna (Lecco, Lombardy, Northern Italy) - Cheng Ji; Andrea Tintori (Diversity)
Here we report and describe a new assemblage of Thylacocephala (Crustacea) from the Early Ladinian Buchenstein Fm. (Middle Triassic) of Grigna, Northern Italy. The assemblage consists of at least four species from three different genera: Ankitokazocaris lariensis sp. n., Ankitokazocaris sp., Austriocaris sp., Stoppanicaris grignaensis gen. et sp. n. This thylacocephalan assemblage is rather diverse compared to the others of the Triassic. The largest size and ornamentation type of thylacocephalan species is compared among different periods of the Triassic and indicates that taxa with ridges on the carapace are generally smaller than those with smooth carapaces. This may be related to their different modes of life, such as inside or above the sediment with low oxygen levels. Large and smooth taxa were possibly more adapted to a life above sandy bottoms in shallow waters, under a somewhat high wave energy, while small, ornamented taxa are better suited for deeper environments with muddy bottoms, inside which they could move freely. The EDS analysis of Austriocaris sp. reveals that the cuticle mainly consists of apatite, which is in accordance with previous interpretations.